2018
DOI: 10.2147/dddt.s154388
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for antiepileptic drugs revisited: a practical approach to establish national guidelines

Abstract: Background and objectiveLaboratories sometimes use different reference ranges for the same antiepileptic drug (AED), particularly for new and poorly investigated drugs. This may contribute to misunderstandings, concerns or inappropriate dose changes, which in turn may affect therapeutic effect, drug safety or treatment adherence. Therefore, the Norwegian Association of Clinical Pharmacology wished to update and harmonize the reference ranges for AEDs and establish national guidelines for Norway.MethodsA workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 53 publications
(81 reference statements)
3
79
1
3
Order By: Relevance
“…10,12 The interaction potential is therefore seen as low, even though interactions with some antacids and analgesics have been reported. 15 The reference range for GBP in epilepsy in Norway is 20-120 µmol/L under drug fasting conditions at steady state, 16 similar to international recommendations. 15 The reference range for GBP in epilepsy in Norway is 20-120 µmol/L under drug fasting conditions at steady state, 16 similar to international recommendations.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…10,12 The interaction potential is therefore seen as low, even though interactions with some antacids and analgesics have been reported. 15 The reference range for GBP in epilepsy in Norway is 20-120 µmol/L under drug fasting conditions at steady state, 16 similar to international recommendations. 15 The reference range for GBP in epilepsy in Norway is 20-120 µmol/L under drug fasting conditions at steady state, 16 similar to international recommendations.…”
supporting
confidence: 67%
“…13,14 Therapeutic drug monitoring is a commonly used tool to optimize treatment of epilepsy 7 and has been used as a part of the comprehensive care approach in epilepsy for 50 years. 15 The reference range for GBP in epilepsy in Norway is 20-120 µmol/L under drug fasting conditions at steady state, 16 similar to international recommendations. 7 The potential benefits of TDM in chronic pain have not been fully realized, 17 despite the widespread use of drugs such as GBP for this indication.…”
supporting
confidence: 67%
“…In a Japanese study the mean PER serum level in responders was 450 ± 361 ng/ml with a range of 85 to 1500 ng/ml [13]. Based on a personal communication from the Dianalund Epilepsy Center in Denmark, a Norwegian report recently proposed a reference range between 86 and 1000 ng/ml [17]. Comparing these reference ranges with our results, our study had one patient with higher plasma concentrations, a good therapy response, and no adverse events at a level of 2436 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Although reference ranges for PER have been proposed based on the data of the pivotal pilot phase III studies [7] or recommendations of the Dianalund Danish Epilepsy Center [17] it is unclear whether a reliable therapeutic range exists. A linear dose-concentration relationship has been reported earlier [7,12,13] and might suggest such a predictable range.…”
Section: Introductionmentioning
confidence: 99%
“…The serum concentration measurements were performed as routine analysis of validated methods at the National Center for Epilepsy, measured by HPLC-UV with a measuring range of 10-250 μmol/L for LCM, on an Ultimate 3000 HPLC, Dionex (125 × 3 mm, 3 μm Hypersil BDS C-18 column) based on Greenway et al 22 We used the reference range of 10-40 μmol/L based on the results from drug-fasting samples in the morning as suggested by Contin et al 23 and Svendsen et al 19 and confirmed as a national reference range. 24 The most recent analysis of LCM and other AEDs at assumed steady-state conditions were included. Blood samples were drawn drug-fasting in the morning before intake of the morning dose as a standard procedure; otherwise, the samples were excluded.…”
Section: Drug Analysismentioning
confidence: 99%